2003
DOI: 10.1063/1.1572811
|View full text |Cite
|
Sign up to set email alerts
|

The phase diagram of the two center Lennard-Jones model as obtained from computer simulation and Wertheim’s thermodynamic perturbation theory

Abstract: The global phase diagram ͑i.e., vapor-liquid and fluid-solid equilibrium͒ of two-center Lennard-Jones ͑2CLJ͒ model molecules of bond length Lϭ has been determined by computer simulation. The vapor-liquid equilibrium conditions are obtained using the Gibbs ensemble Monte Carlo method and by performing isobaric-isothermal NPT calculations at zero pressure. In the case of the solid phase, two close-packed solid structures are considered: In the first structure, the molecules are located in layers and all molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 64 publications
(83 reference statements)
6
30
0
Order By: Relevance
“…Closely related apolar dumbbell systems show formation of an amorphous solid phase at similar temperatures [43]. We also observe solidification in our systems at low temperature and this is a likely explanation for these peaks.…”
Section: Resultssupporting
confidence: 77%
“…Closely related apolar dumbbell systems show formation of an amorphous solid phase at similar temperatures [43]. We also observe solidification in our systems at low temperature and this is a likely explanation for these peaks.…”
Section: Resultssupporting
confidence: 77%
“…equation (65) is useful not only for ice but for other disordered solids as well. In fact it can be applied successfully [158,159,32,160,38] to tangent dimers, formed by two tangent spheres, where Nagle [161] has estimated Ω, and for fully flexible hard sphere chains [42](where Flory and Huggins [162,163] have estimated Ω).…”
Section: Einstein Crystal Calculations For Disordered Systemsmentioning
confidence: 99%
“…Of course for a simple fluid (HS, LJ) there are no orientational degrees of freedom so that in the Einstein molecule approach, atom 1 is fixed. Fixing the position of one molecule avoids the quasi-divergence of the integrand of equation (38) when the coupling parameter λ tends to zero. The computational implementation of the method as well as the derivation of the main equations is rather simple.…”
Section: The Einstein Molecule Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…
AbstractBy using canonical Monte Carlo simulation, the liquid-vapor phase diagram, surface tension, interface width, and pressure for the Mie(n,m) model fluids are calculated for six pairs of parameters m and n. It is shown that after certain re-scaling of fluid density the corresponding states rule can be applied for the calculations of the thermodynamic properties of the Mie model fluids, and for some real substances.
PACS numbers:1 Among the intermolecular effective interaction potentials, the Lennard-Jones one is by far the most widely used for approximating the physics of simple nonpolar molecules in all phases of matter [1,2,3,4,5,6,7,8,9,10,11,12]. The attractiveness of the LJ model is mainly due to its more convenient mathematical form than to its accuracy in representing the properties of real fluids.
…”
mentioning
confidence: 99%